Análisis de las propiedades mecánicas de la aleación aluminio AA6063 en el proceso de homogenizado en la Empresa Cedal S.A. - Hinojosa Iza, Jorge Manuel (2018)
As industries grow, they try to standardize their manufacturing processes to deliver a finer and more durable material to their consumers based on improving the properties of metals according to the need to have a quality product in order to be able to compete in the market. That is why this research had as aim to analyze the changes in mechanical properties in order to identify a standard time of homogenization, varying the holding time of homogenized between (4.5 and 6 hours) at a temperature of 560 ° C it is expected to obtain different mechanical characteristics. It was carried out material testing specifically of spectrometry, hardness, tension, grain size and microstructure, taking as guide the ASTM standards. The research work compares the mechanical strength, elongation, hardness, grain size and microstructural changes between the tested specimens, based on the written report it was identified that the optimal time for the homogenization support time is of 5 hours at a temperature of 560 ° C having mechanical characteristics suitable for the AA6063 aluminum alloy. The control of temperature in the different points, the follow-up of the test pieces and the machining of the witnesses is the proposal that guarantees the research, the stability and thus be able to relate them to the changes of the mechanical properties.